In Pursuit of Next Generation N-Heterocyclic Carbene-Stabilized Copper and Silver Precursors for Metalorganic Chemical Vapor Deposition and Atomic Layer Deposition Processes - Ilamparithy Selvakumar; Nils Boysen; Marco Bürger; Anjana Devi (Chemistry, 2023)
Volatile, reactive, and thermally stable organometallic copper and silver complexes are of significant interest as precursors for the metalorganic chemical vapor deposition (MOCVD) and atomic layer deposition (ALD) of ultra-thin metallic films. Well-established CuI and AgI precursors are commonly stabilized by halogens, phosphorous, silicon, and oxygen, potentially leading to the incorporation of these elements as impurities in the thin films. These precursors are typically stabilized by a neutral and anionic ligand. Recent advancements were established by the stabilization of these complexes using N-heterocyclic carbenes (NHCs) as neutral ligands. To further enhance the reactivity, in this study the anionic ligand is sequentially changed from β-diketonates to β-ketoiminates and β-diketiminates, yielding two new CuI and two new AgI NHC-stabilized complexes in the general form of [M(NHC) (R)] (M = Cu, Ag; R = β-ketoiminate, β-diketiminate). The synthesized complexes were comparatively analyzed in solid, dissolved, and gaseous states. Furthermore, the thermal properties were investigated to assess their potential application in MOCVD or ALD. Among the newly synthesized complexes, the β-diketiminate-based [Cu(tBuNHC) (NacNacMe)] was identified to be the most suitable candidate as a precursor for Cu thin film deposition. The resulting halogen-, oxygen-, and silicon-free CuI and AgI precursors for MOCVD and ALD applications are established for the first time and set a new baseline for coinage metal precursors.